Annual Plan 2003-2004 Government of Andhra Pradesh - Planning Commission (Planning Commission, 2003)
Vision 2020 of the state has articulated the development goals to be achieved in different sectors by the year 2020. The mission is to make Andhra Pradesh the foremost state in the country in terms of growth, equity and quality of life. The goal is to eradicate poverty and to ensure that every man, woman and child in the state has access, not just to basic minimum needs, but to all the opportunities to lead a happy and fulfilling life. The strategy for achieving the goals set in Vision 2020 calls for accelerating economic growth focusing on the distinctive strength of the state in each region by identifying the growth engines, building the capabilities of the state's people focusing on human development and providing responsive governance.
Planning Department, Government of Andhra Pradesh